2021
DOI: 10.21037/apm-21-3425
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of traditional Chinese medicine compound in treating infertility caused by endometriosis

Abstract: Background: To perform meta-analysis to investigate the efficacy and safety of traditional Chinese medicine (TCM) compound in the treatment of endometriosis (EMS)-induced infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
1
6
0
2
Order By: Relevance
“…At present, many studies have shown that TCM has a synergistic effect on the treatment of endometriosis. 26,27 The mechanisms involved include regulating the immune response, apoptosis, and angiogenesis, 28 which are consistent with our findings. However, many studies use Chinese herbal medicine directly, and the quality control may be unstable.…”
Section: Discussionsupporting
confidence: 89%
“…At present, many studies have shown that TCM has a synergistic effect on the treatment of endometriosis. 26,27 The mechanisms involved include regulating the immune response, apoptosis, and angiogenesis, 28 which are consistent with our findings. However, many studies use Chinese herbal medicine directly, and the quality control may be unstable.…”
Section: Discussionsupporting
confidence: 89%
“…The non-Cochrane systematic review by Dong et al concluded that traditional Chinese medicine may be effective in increasing the response rate and pregnancy rate compared to ‘Western’ medicine. However, these outcomes were not clearly defined within the article, with significant heterogeneity between studies and possible selection and attrition bias in their analysis [42].…”
Section: Non-medical Treatment Strategiesmentioning
confidence: 99%
“…(11)(12)(13) A fisioterapia tem se destacado no tratamento de condições pélvicas dolorosas através do uso de técnicas de reabilitação neuromuscular, como biofeedback, eletroestimulação e cinesioterapia; e de técnicas que promovem analgesia como, a corrente TENS. (14)(15)(16)(17)(18)(19) O objetivo geral desta pesquisa consiste em analisar os benefícios da fisioterapia e quais são as técnicas mais utilizadas para a redução dos sintomas de dor da endometriose. A escolha do tema se deu pela necessidade de maiores entendimentos que norteiem a atuação do profissional em fisioterapia frente à pacientes que fazem tratamento para alívio da dor pélvica crônica e saber se os métodos fisioterapêuticos são eficazes para a redução da dor em mulheres com endometriose.…”
Section: Introductionunclassified